Was macht die Digitalisierung mit der Politik? Einwürfe und Provokationen - Schmidt, Robin; Klein, Björn (De Gruyter, 2022)
What role does digitality play in negotiating the question of how we want to live together in the future? How do processes of digitalisation affect the formation of opinion, the shaping of political parties, their communication with voters, the discursive formation of issues, the creation of majorities and their regulation? This volume offers a constructive perspective on the challenges of a society increasingly shaped by digitalisation. In addition to diagnoses of the current situation, the contributions also bring together concepts and speculative drafts for the future that are united by the concern for a more just society. Experts from academia, journalism and practice outline the central results of the second "Dießener Klausur Mensch|Maschine|Zukunft" (Dießen Retreat Man|Machine|Future), which creates a space for constructive drafts, interjections and provocations in today's discourse on digitalisation, which is often characterised by cultural criticism and pessimistic perspectives.